A multi-level approach to reduce exploding type 2 diabetes in Pakistan - Jamil, Fazal; Mir, Umaima; Niazi, Anum G.; Kifayat, Shandana; Kifayat, Shanlina; Shafiq, Sobia; Wali, Zeeshan; Khan, Muhammad Ali Jan; Wali, Baber; Kobra, Khadija Tul; Khan, Muhammad Salar (Frontiers in Public Health, 2025)
Pakistan has the third-highest rate of type 2 diabetes globally, following China and India, making this a significant public health crisis. Despite the severity of the issue, efforts from health and policy practitioners to address it remain limited. With millions already diagnosed as pre-diabetic, the rising incidence of diabetes is rapidly becoming a public health emergency that demands immediate attention. This policy brief provides an accessible overview of diabetes, focusing on its types, mechanisms, and preventive measures. It also identifies key contributing factors, such as dietary habits, obesity, physical inactivity, and the influence of modern dietary trends, while proposing strategies for individuals, communities, and policymakers to combat this growing epidemic in Pakistan. The brief emphasizes the need for a multi-level approach that includes public awareness, education, behavioral and dietary changes, and policy interventions to reverse the trend. Strategies discussed include promoting healthy eating, increasing physical activity, managing obesity, and enhancing access to affordable, healthy food. Additionally, the brief highlights the importance of community and government support, such as public health campaigns, infrastructure improvements, and legislative efforts. By adopting this comprehensive approach, Pakistan can take meaningful steps to address the diabetes epidemic and improve public health outcomes.